2011
DOI: 10.1542/peds.2010-1656
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Ethnic, and Socioeconomic Disparities in the Prevalence of Cerebral Palsy

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Black infants have an increased risk of cerebral palsy when compared with white infants. The reason for this racial disparity is unclear. Lower socioeconomic status may be associated with an increased risk of cerebral palsy. WHAT THIS STUDY ADDS:The increase in cerebral palsy among blacks is due to higher rates of low birth weight. Among low birth weight infants, blacks are less likely to have cerebral palsy than whites. Prenatal care and maternal education also impact cerebral pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 33 publications
9
89
0
3
Order By: Relevance
“…A cross-sectional study of California children with CP born between 1991 and 2001 found that this disparity was attributable to the higher frequency of VLBW and MLBW among NHB children. 14 Recently, the Autism and Developmental Disabilities Monitoring (ADDM) Network reported a similar disparity, with higher CP prevalence among NHB compared with NHW children, which remained after adjustment for maternal education. 15 It is unclear whether these racial/ ethnic differences in CP prevalence in the United States have persisted over time.…”
mentioning
confidence: 97%
“…A cross-sectional study of California children with CP born between 1991 and 2001 found that this disparity was attributable to the higher frequency of VLBW and MLBW among NHB children. 14 Recently, the Autism and Developmental Disabilities Monitoring (ADDM) Network reported a similar disparity, with higher CP prevalence among NHB compared with NHW children, which remained after adjustment for maternal education. 15 It is unclear whether these racial/ ethnic differences in CP prevalence in the United States have persisted over time.…”
mentioning
confidence: 97%
“…13 Numerous other sociodemographic, economic, biologic or psychosocial variables are typically included in these regressions. Some of these variables may be thought of as potentially on the pathway between race/ethnicity and the health outcome.…”
mentioning
confidence: 99%
“…Risk factors and casual pathways for CP was the most prevalent theme for this aim, and included investigation of maternal risk factors [115120], genetics [121124], term birth [125128] and labor and delivery [37,129,130]. Other topics of research included preterm risk factors [131,132], reproductive technology [133,134], multiples [135,136], infant infection, [137] MRI findings and risk factors [138] ethnic/socioeconomic disparities [139] and predicting outcomes [140]. The two other Prevention studies related to predicting outcomes were classified concurrently with the Planning aim (Table S5) [141,142].…”
Section: Resultsmentioning
confidence: 99%